Helium permeation as a fast quality indicator for barrier properties of solar cell encapsulates. (2nd August 2017) - Schulze, Stefan‐H.; Ehrich, Christian; Meitzner, Rico; Pander, Matthias
Abstract: The advent of flexible electronic devices and flexible thin‐film photovoltaic modules increases the need for transparent and flexible high‐barrier films. Conventional methods for measuring the barrier properties of such films are costly and time consuming. In our work, we present a method where we correlate water vapor and helium transmission rate measurements on strained barrier films with thin‐film solar module performance. We show that the detected properties correlate well with the performance of a CIGS mini module exposed to damp‐heat environment. The critical strain limit for a substantial decrease in barrier properties was identified for an ETFE‐based barrier film incorporating an inorganic barrier layer. It was found that the detection of the helium transmission rate provides a fast and reliable way to identify damage to barrier films and is therefore suitable as means for quality control or incoming goods inspection.